Co-digestão anaeróbia de dejetos de bovinos e dois tipos de glicerina bruta - Bertozzo, Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
A glicerina bruta é um resíduo da produção de biodiesel de baixo valor agregado, no entanto, possui alto teor de carbono e potencial para produzir bons resultados se co-digerida de maneira anaeróbia com um material rico em nitrogênio como os dejetos de animais. Sendo assim, objetivou-se com este trabalho avaliar a co-digestão de dejetos de bovinos leiteiros e dois tipos de glicerina bruta: bruta e bruta loira, em biodigestores anaeróbios operados em sistema semi-contínuo, sob delineamento experimental inteiramente casualizado com cinco repetições por tratamento, sendo DBL – dejetos de bovinos leiteiros + água; DBL+GB – dejetos de bovinos leiteiros + glicerina bruta + água; DBL+GL – dejetos de bovinos leiteiros + glicerina bruta loira + água. As cargas diárias foram iniciadas tanto no DBL+GB como no DBL+GL com 1,25% de glicerina bruta passando em seguida para 2,5; 5; 7,5, 10, 15 e 20%; os aumentos nas porcentagens foram graduais e realizados a cada 30 dias, sendo este o TRH estabelecido. Os parâmetros avaliados foram: pH, acidez volátil (AV), alcalinidade total (AT), relação AV/AT, temperatura, reduções dos teores de sólidos totais (ST) e de sólidos voláteis (SV), produção de biogás/dia, teor de metano (CH4), potencial de produção de biogás por quilograma: de substrato (m3 kg-1 subst.), de sólidos totais adicionados (m3 kg-1ST adic.), de sólidos voláteis adicionados (m3 kg-1 SV adic.) e de dejetos de bovinos leiteiros (m3 kg-1 dej.), teores de...

Crude glycerin is a waste from biodiesel production with a low added value, however, it has a high carbon content and potential to produce good results if it is co-digested with a rich nitrogen material as animal manures. This way, the aim of this study was the co-digestion evaluation of dairy cattle manures and two types of crude glycerin: crude and blonde crude, in anaerobic digesters operated in semi-continuous system, under experimental design entirely randomized with 5 repetitions for each treatment, DBL – dairy cattle manures + water; DBL+GB - dairy cattle manures + crude glycerin + water; DBL+GL - dairy cattle manures + blonde crude glycerin + water. Daily loads were initiated both in DBL+GB and DBL+GL with 1,25% of crude glycerin and then rising to 2,5; 5; 7,5, 10, 15 and 20%; increases in percentages were made gradually and every 30 days. The parameters assessed were: pH, volatile fatty acids (VFA), total alkalinity (TA), VFA/TA ratio, temperature, removal of total solids (TS) and volatile solids (VS), biogas production, methane rate (CH4), potential of biogas production per kilogram: of substrate (m3 kg-1 subst.), total solids added (m3 kg-1 TS add.), volatile solids added (m3 kg-1 VS add.) and dairy cattle manures (m3 kg-1 dej.), nitrogen, phosphorus, potassium, carbon and organic matter content and carbon/nitrogen ratio. Least Square Means statistics was used to analyze the data (p<0,05). DBL+GB and DBL+GL treatments provided increments in biogas production in relation to DBL in all crude glycerin percentages tested. CH4 contents have been satisfactory and always above 59%, in all treatments. The ST and VS removals from DBL were less than DBL+GB and DBL+GL, and in these, increases in crude glycerin quantities accompanied. Potentials of biogas production varied according to the analyzed parameter: per kg of substrate and per kg of manures were higher in DBL+GB and in DBL+GL ...
Keywords: Biodigestor; Biogas; Residuos de animais; Glicerina; Residuos organicos; Organic wastes - Recycling